Climate change impact to coastal communities in Kudat, Sabah, Malaysia - Nurrul Fazlina Osman; Ejria Saleh; Nurulain Ismail; Justin Sentian (Faculty of Science and Natural Resources, 2021)
Climate change is among major threats to marine ecosystems, representing both a challenge and an opportunity for researchers and the government. Impacts are not experienced uniformly, and the existing unbalanced ecosystem will be further exacerbated without urgent action to mitigate climate change and enhance community resilience. The objective of this study is to draw on insights on the impact of climate change based on the coastal community input and environment change at Kg. Kimihang, Kelambu Beach and Bavang Jamal, Kudat, Sabah. Interview and fieldworks were carried out in March and August 2020. The unstructured questionnaire was applied to 15 respondents to know in-depth their experiences. The data were presented as timeline narration before and after the year 2000. Results show that the respondents address climate change through the reduction of their yield on natural resources and the change of the surrounding environment, change of career paths, and the existence of structural management around the Kudat area. The coastal communities are also needed education and awareness programmed to manage their coastal area and the maximized use of their resources in a sustainable manner. This is to suggest that constructing the best adaptation strategies requires attention.